RobotSLAM: A Lightweight Low-cost 3D LiDAR SLAM Handheld Device - H. Gao; G. Kong; X. Huang; H. Fan; R. Zhong (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
As the importance of Mobile Laser Scanning (MLS) technology in 3D mapping continues to grow, the development of low-cost, portable devices to address the complex mapping needs of various environments has become a key area of research in the industry. Currently, handheld MLS devices are increasingly being applied in a wide range of surveying tasks, especially in small outdoor spaces, indoor environments, and narrow areas with limited accessibility. This study proposes the development of a novel handheld mobile laser scanning system, RobotSLAM Lite. The system integrates a LiDAR sensor and a fisheye camera through a multi-sensor fusion approach to enable Simultaneous Localization and Mapping (SLAM). A dedicated data processing platform, RobotSLAM Engine, has also been developed to generate and optimize point cloud maps with true-color information. To evaluate the system’s performance, the study was conducted at the Norwegian University of Science and Technology, utilizing an experimental building and nearby roads as test sites. High-precision point cloud data obtained from a terrestrial laser scanner (Leica ScanStation P30 TLS) and RTK measurement Ground Control Points (GCPs) were used as reference benchmarks. A four-metric evaluation framework, comprising absolute coordinate deviation, point cloud density distribution, surface roughness, and cloud-to-cloud distance (C2C), was established to quantitatively analyze the mapping accuracy of the device in indoor and outdoor scenarios at various scales. Experimental results indicate that RobotSLAM Lite provides centimeter-level accuracy while significantly reducing both equipment cost and operational complexity, offering a new technological solution for 3D mapping in both large and small spaces.